Pengembangan Berpikir Kreatif dalam Aktivitas Pembelajaran pada Masa Pandemic Covid-19 melalui Media Quizizz - Asih Andriyati Mardliyah; Rizky Oktaviana E.P; Fitriana Nadila (Jurnal Pengabdian Masyarakat (abdira), 2022)
The Learning from Home Policy has caused problems for teachers and students of SMK Palapa Mojokerto. The number of teachers who still lack technology is an obstacle in delivering materials and assignments during online learning. During online teaching and learning activities, teachers usually only transfer materials and assignments via WA Group. Therefore, this devotion aims to increase teachers' understanding of the development of creative thinking and equip teachers with skills so that they can use quiziz media as a learning medium to improve students' creative thinking during the covid 19 pandemic. The implementation of this community service uses an approach method with training activities through media zoom with two sessions, namely the first session, delivering creative thinking material, the second session, delivering material on Quizizz. The result of the devotional activity is; Increased teacher knowledge on the development of creative thinking and skills using quizizz in the learning process.